Interactive technologies for autism - Kientz, Julie A.; Goodwin, Matthew S.; Hayes, Gillian R. (Gillian Rachael); Abowd, Gregory D., 1964- ([San Rafael, California (1537 Fourth Street, San Rafael, CA 94901 USA)] : Morgan & Claypool Publishers, 2014)
Development, deployment, and evaluation of interactive technologies for individuals with autism have been rapidly increasing over the last decade. There is great promise for the use of these types of technologies to enrich interventions, facilitate communication, and support data collection. Emerging technologies in this area also have the potential to enhance assessment and diagnosis of individuals with autism, to understand the nature of autism, and to help researchers conduct basic and applied research. This book provides an in-depth review of the historical and state-of-the-art use of technology by and for individuals with autism. The intention is to give readers a comprehensive background in order to understand what has been done and what promises and challenges lie ahead. By providing a classification scheme and general review, this book can also help technology designers and researchers better understand what technologies have been successful, what problems remain open, and where innovations can further address challenges and opportunities for individuals with autism and the variety of stakeholders connected to them.
Includes bibliographical references (pages 111-149).
Keywords: Autistic people; Assistive computer technology; Computers and people with disabilities; Attention-deficit hyperactivity disorder; Autism -- History; Autism; Autistic children